Analisis Indeks Kesesuaian Lokasi Garam (IKG) di Kawasan Sentra Produksi Garam Jawa Timur - Andi Kurniawan; Riski Agung Lestariadi; Rika Kurniaty; Tri Budi Prayodo; Citra Satrya Utama Dewi; Abd Aziz Amin; Adi Tiya Yanuar; Lutfi Ni'matus Salamah (Universitas Trunojoyo Madura, 2020)
Salt is an essential commodity that is widely used for consumption and industrial purposes. One of the main factors determining the success of this salt production is the suitability of the salt production location. However, there has been no analysis of the suitability of salt production locations in salt production centers in East Java. This study aims to analyze the suitability level of the location of salt production centers for the salt production process using the Salt Location Suitability Index (IKG). The areas analyzed in this study are salt production centers in Sampang Regency, Probolinggo Regency, Gresik Regency, and Tuban Regency. The IKG analysis is prepared based on nine suitability parameters: rainfall, soil permeability, soil type, duration of exposure, humidity, wind speed, air temperature, evaporation rate and saturation level of raw material water. The IKG analysis results can also be used as a basis for recommending alternative technologies that need to be applied to increase salt production. The results of this study indicate that the locations of salt production in Sampang District, Probolinggo Regency and Tuban Regency, which are the focus of this study, are in the Very Appropriate category (more than 85%), while the locations in Gresik Regency are in the Sufficiently Suitable category (80-84 %). Based on the results of this study, all the locations that are the focus of this study are suitable for further development of salt production.